Defects in flat and pitched roofs for houses below three storey / Muhammad Hazim Abdul Jamal - Abdul Jamal, Muhammad Hazim (Faculty of Architecture, Planning and Surveying, 2015)
This study is focus on defects in flat and pitched roof for houses below 3-storey. There are many type of roof the typical that been used in housing area in Malaysia is Flat roof and pitched roof. All type of roofs cannot run from a problem which is defect. The defects can be categorized as minor defect or major defect. Minor defect only affect the aesthetic value of the roof area and major defect can causes accident happens to the occupant or the property. Defects can be occur whether on design or construction stage, or after a few years time. In order to minimize defects in roof, the design stage for the roof must be studied well. The construction stage of the roof is also important to minimize the defects on roof after a few years time. In other hand, the occupant itself must concerned about the defects that can be seen on their roof Defects come from many causes such as aging, weather, poor workmanship and other. By knowing the causes, we can avoid the defects become worst. This dissertation have included five chapters where discuss the type of defects, causes of the defects and how to overcome the defects. The research data are collected from three case study which is Bandar Baru Bangi, Shah Alam and Seri Kembangan. The data will be analyzed by doing questionnaires and condition survey on the roof elements. On the whole, the conclusion and recommendations will be provided in order to support this dissertation.